2018
DOI: 10.1002/ame2.12033
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiome and Alzheimer's disease: A review

Abstract: Alzheimer's disease ( AD ) is an increasingly common neurodegenerative disease. Since the intestinal microbiome is closely related to nervous system diseases, alterations in the composition of intestinal microbiota could potentially contribute to the pathophysiology of AD . However, how the initial interactions with intestinal microbes alter events later in life, such as during neurodegenerative diseases, is still unclear. This review summarizes what is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 119 publications
(140 reference statements)
1
58
0
Order By: Relevance
“…The remodeling of the microbial pattern extends the research performed so far and opens up theories that will reconsider the introduction of new strains into the human microbial ecosystem by modifying/decreasing the bioavailability of some essential functional compounds [75]. This is a secondary explanation for the reduction of colonic bioavailability, microbial plasticity, and the incidence of degenerative diseases [76].…”
Section: The Causes Of Disruption Of the Microbiota-mediated Responsementioning
confidence: 84%
“…The remodeling of the microbial pattern extends the research performed so far and opens up theories that will reconsider the introduction of new strains into the human microbial ecosystem by modifying/decreasing the bioavailability of some essential functional compounds [75]. This is a secondary explanation for the reduction of colonic bioavailability, microbial plasticity, and the incidence of degenerative diseases [76].…”
Section: The Causes Of Disruption Of the Microbiota-mediated Responsementioning
confidence: 84%
“…Ever since the first completion of a whole genome of a free-living organism in 1995, numerous studies on microbes and viruses for genome sequencing have been conducted and are still in progress with further investigations of their relation to human health and diseases [7][8][9][10]. Recently, several studies have focused on how the gut microbiota influence health and diseases and had promising results concerning autoimmune diseases, such as Crohn's disease, systemic lupus erythematosus (SLE) and autoimmune uveitis [11][12][13][14][15][16]. Intestinal epithelial cells are reported to play an essential role in balancing gut microbiota and their metabolic changes can result in dysbiosis in certain autoimmune diseases [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite current treatment approaches for dry eye syndrome (DES) [ 14 , 15 ], there are still unmet needs that require the development of new interventions for SS subjects. Recent studies have revealed gut microbiota to be critical in Crohn’s disease, systemic lupus erythematosus (SLE), autoimmune uveitis, and SS-related ocular surface disease [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. As with autoimmune diseases, metabolic diseases and the distant brain are also influenced by gut microbiota [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%